Drug Encapsulated Lipid-Polymeric Nanohybrid as a Chemo-therapeutic Platform of Cancer - Kumar R.; Ranjan Srivastava V.; Mahapatra S.; Dkhar D.S.; Kumari R.; Darshna; Prerna K.; Dubey V.K.; Chandra P. (My University, 2025)
The focus of this research is to design a bioengineered drug delivery vehicle that is efficient in anti-cancer drug delivery in a controlled manner. The experimental work focuses on constructing a methotrexate-loaded nano lipid polymer system (MTX-NLPHS) that can transport methotrexate (MTX) in MCF-7 cell lines in a controlled manner through endocytosis via phosphatidylcholine. In this experiment, MTX is embedded with polylactic-co-glycolic acid (PLGA) in phosphatidylcholine, which acts as a liposomal framework for regulated drug delivery. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and dynamic light scattering (DLS) were utilized to characterize the developed nanohybrid system. The particle size and encapsulation efficiency of the MTX-NLPHS were found to be 198 ± 8.44 nm and 86.48 ± 0.31 %, respectively, which is suitable for biological applications. The polydispersity index (PDI) and zeta potential of the final system were found to be 0.134 ± 0.048 and-28 ± 3.50 mV, respectively. The lower value of PDI showed the homogenous nature of the particle size, whereas higher negative zeta potential prevented the system from agglomeration. An in vitro release kinetics was conducted to see the release pattern of the system, which took 250 h for 100% drug release This kind of system may carry the drug for a long time in the circulatory system and prevent the drug discharge. Other cell culture assays such as 3-(4, 5-dimethyl thiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) and reactive oxygen species (ROS) monitoring were used to see the effect of inducers on the cellular system. MTT assay showed cell toxicity of MTX-NLPHS reduced at the lower concentration of the MTX, however, toxicity increased at the higher concentration of the MTX as compared to free MTX. ROS monitoring c revealed more scavenging of ROS using MTX-NLPHS as compared to free MTX. Confocal microscopy suggested the MTX-NLPHS induced more nuclear elongation with cell shrinkage comparatively. © The author(s).